A Survey of Ethics Curriculum in Canadian Initial Teacher Education - Maxwell, Bruce; Tremblay-Laprise, Audrée-Anne; Filion, Marianne (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
This paper reports the results of a survey on ethics education in initial teacher education in Canada. Using an online survey and an academic calendar analysis, data was collected on ethics course requirements, perceptions about ethics content, institutional factors mediating the implementation of ethics courses, and teaching and learning objectives. Unexpectedly, the results showed that a required ethics course is as common in teacher education in Canada as it is in medical education and that an ethics curriculum is regarded highly by Canadian teacher educators as an aspect of teacher education. The paper concludes by suggesting directions for future research and underlining the need for network building in the area of ethics education for teachers in Canada.